2019
DOI: 10.3390/ijerph16214103
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Hong Kong Chinese version of the Support Person’s Unmet Needs Survey—Short Form

Abstract: This study describes the psychometric properties of a Hong Kong Chinese version of the short form of the Support Person’s Unmet Needs Survey (SPUNS-SF) for caregivers of patients with cancer. A convenience sample of 280 patient-caregiver dyads was recruited between April and June 2018. A subsample of 70 caregivers completed the survey again, two weeks later. A confirmatory factor analysis (CFA) examined the instrument’s factorial structure, ordinal alpha coefficients evaluated the internal consistency, and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Items were measured on a five-point Likert-type scale ranging from 1 (Not at all) to 5 (Very much). Items 4,10,12,16,22,27,28, and 34 were reverse coded. Total score was computed by summing up all the items, with higher score indicating lower quality of life.…”
Section: Caregiver Quality Of Life Index-cancer (Cqol-c)mentioning
confidence: 99%
See 1 more Smart Citation
“…Items were measured on a five-point Likert-type scale ranging from 1 (Not at all) to 5 (Very much). Items 4,10,12,16,22,27,28, and 34 were reverse coded. Total score was computed by summing up all the items, with higher score indicating lower quality of life.…”
Section: Caregiver Quality Of Life Index-cancer (Cqol-c)mentioning
confidence: 99%
“…Several instruments have been developed to assess caregiver needs, such as the Cancer Caregiving Tasks, Consequences and Needs Questionnaire (CaTCoN) [10,11], Cancer Survivors' Partners Unmet Needs (CaSPUN) [12], Cancer Support Person's Unmet Needs (SPUNS) [13], Comprehensive Needs Assessment Tool for Cancer-Caregivers (CNAT-C) [14], and the Needs Assessment of Family Caregivers-Cancer (NAFC-C) [15]. Both the SPUNS and the CNAT-C have been validated and translated for use in Chinese populations [16,17]. However, only the NAFC-C, has been developed on a conceptual framework based on the Need Fulfillment Theory which enhances its clinical utility [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Local research has also reported this similar finding, indicating that caregivers have unmet support needs in personal care, practical household support, providing personal care, financial, legal and work issues, and equipment to care for patients. 30,31 The current findings suggest that there is an urgent need to ease caregiver burden by designing services to address their unmet needs.…”
Section: Discussionmentioning
confidence: 87%
“…Two studies focused on the carer. Leung and colleagues [ 9 ] carried out the validation of the Support Person’s Unmet Needs Survey Short Form to measure the unmet needs of family caregivers taking care of cancer patients in the Hong Kong Chinese population. Using confirmatory factor analysis (CFA), the five-factor structure of the original scale, consisting of information, future concerns, work and finances, healthcare access and continuity, and personal and emotional needs, was replicated.…”
Section: Included Workmentioning
confidence: 99%